2023
DOI: 10.1186/s12906-023-03979-w
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of extracts and compounds from Thai Kae-Lae (Maclura cochinchinensis (Lour.) Corner)

Abstract: Background and aims The purpose of this study was to investigate the biological properties of Kae-Lae (Maclura cochinchinensis (Lour.) Corner), a traditional medicinal plant used in Ayurvedic recipes in Thailand. To achieve this objective, heartwood samples were collected from 12 sources across Thailand. Fractional extracts (n-hexane, ethyl acetate, and ethanol) and the dominant compounds (morin, resveratrol, and quercetin) were examined for their abilities on cytotoxicity, antioxidant, anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Chewchinda et al reported a yield of 18.99 ± 0.65% w / w after boiling dried heartwood powder in distilled water, followed by filtration and spray drying of the filtrate [ 13 ]. Furthermore, Rueankham et al determined that ethanol extraction produced the highest yields, ranging from 5.18% to 9.56% when examining the effects of solvents of varying polarities [ 16 ]. These outcomes highlight the crucial influence of solvent selection on the efficiency of extracting bioactive compounds from M. cochinchinensis heartwood, emphasizing the significance of strategic solvent choice to enhance yields.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chewchinda et al reported a yield of 18.99 ± 0.65% w / w after boiling dried heartwood powder in distilled water, followed by filtration and spray drying of the filtrate [ 13 ]. Furthermore, Rueankham et al determined that ethanol extraction produced the highest yields, ranging from 5.18% to 9.56% when examining the effects of solvents of varying polarities [ 16 ]. These outcomes highlight the crucial influence of solvent selection on the efficiency of extracting bioactive compounds from M. cochinchinensis heartwood, emphasizing the significance of strategic solvent choice to enhance yields.…”
Section: Resultsmentioning
confidence: 99%
“…The modest antioxidant activities observed in fractions FA and FM could potentially be explained by the considerable presence of impurities within these fractions. Nonetheless, the antioxidant efficacy of fraction FA is presumably derived from its constituents of resveratrol and oxyresveratrol, while the antioxidant capability observed in fraction FM is likely attributable to morin and a variety of flavonoids and xanthones [ 9 , 16 , 39 ]. The pronounced yellowish pigment observed in the fraction FM could potentially be attributed to morin, a predominant compound in the heartwood of M. cochinchinensis [ 16 ], known for its array of biological properties, including antioxidant, anti-inflammatory, and antidiabetic activities [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thai culture has, for many years, included the use of M. cochinchinensis as a medicine against skin diseases, diarrhea, chronic fever, and lymph node abnormalities. In the cochinchinensis species, the presence of morin has been determined as one of the most abundant compounds, so its presence in Maclura suggests its high potential as an antioxidant, anti-inflammatory, and anticancer source [70].…”
Section: Maclura Cochinchinensis (Lour) Cornermentioning
confidence: 99%